Le mur intrapsychique chez le sujet métissé - Sonia Gérard (Cahiers du MIMMOC)
In the field of mixed couples, the very formation of the couple implies intercultural borders. The birth of children, which activates the “mixing” process, may have a possible effect on these borders which are often represented as walls. Therefore the wall paradigm has a very heuristic function insofar as it allows the modelization of psychical phenomenon through representations using vision and touch. This paper considers various functions of the Berlin wall in order to understand processes such as cleaving and its resolution.